Fuzzy modeling and event-triggered control of offshore platforms under constrained bandwidth: an encoding-decoding scheme - Yang, Yekai; Niu, Yugang; Li, Jiarui (Nonlinear dynamics, 2025)
This study investigates the fuzzy modeling and event-triggered control problems for nonlinear offshore platforms under encoding-decoding scheme (EDS), where an active mass damper (AMD) mitigates the platform vibrations induced by wave forces. First, the platform system with inherent nonlinearities is modeled via Takagi-Sugeno fuzzy technique. Under the limited bandwidth, event-triggering mechanism (ETM) and EDS are implemented for reducing communication resource usage. Given the distance between sensors installed on the platform and AMD, decentralized ETMs are developed to independently manage the signal transmission of each sensor. Besides, a dynamic quantizer and encoding function under limited coding length are deigned to convert triggered state into a binary string, i.e., codeword. Subsequently, a decoder is proposed to restore state signal and design fuzzy controller. Meanwhile, slack matrices integrated with membership function boundary information are utilized to derive sufficient conditions, and the relationship between control performance and coding error is clearly established. Finally, simulation results verify the vibration reduction performance in offshore platforms.